Global health: A lasting partnership in paediatric surgery - Kokila Lakhoo; David Msuya (Wolters Kluwer Medknow Publications, 2015)
Background: To emphasise the value of on-going commitment in Global Health Partnerships. Materials and Methods: A hospital link, by invitation, was set up between United Kingdom and Tanzania since 2002. The project involved annual visits with activities ranging from exchange of skill to training health professionals. Furthermore, the programme attracted teaching and research activities. For continuity, there was electronic communication between visits. Results: Six paediatric surgeons are now fully trained with three further in training in Africa. Paediatric surgery services are now separate from adult services. Seven trainee exchanges have taken place with four awarded fellowships/scholarships. Twenty-three clinical projects have been presented internationally resulting in eight international publications. The programme has attracted other health professionals, especially nursing and engineering. The Tropical Health and Education Trust prize was recently achieved for nursing and radiography. National Health Service has benefited from volunteering staff bringing new cost-effective ideas. A fully funded medical student elective programme has been achieved since 2008. Conclusion: Global Health Partnerships are an excellent initiative in establishing specialist services in countries with limited resources. In the future, this will translate into improved patient care as long as it is sustained and valued by long term commitment.